2003
DOI: 10.1207/s15548430jlr3501_4
|View full text |Cite
|
Sign up to set email alerts
|

Constructing Literacy: How Goals, Activity Systems, and Text Shape Classroom Practice

Abstract: Interviewer: What does it mean to be a reader in this class? Students:To know what you're reading about. Not just reading the words, but understand. I love to read.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…However, the experience of a student's "being" as an event in all its supposed uniqueness is compensated by "tightening" discipline in the university on the basis of strengthening administrative control. Therefore, the subject of educational activity has an image of the "World" formed on the basis of intellectual and cognitive actions transformed into object-and-practical ones [10]. The author's idea is to let a student, as a subject of educational and professional activities, manifest subjectivity in relation to the object, namely, professionally significant qualities of the person.…”
Section: Problem Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the experience of a student's "being" as an event in all its supposed uniqueness is compensated by "tightening" discipline in the university on the basis of strengthening administrative control. Therefore, the subject of educational activity has an image of the "World" formed on the basis of intellectual and cognitive actions transformed into object-and-practical ones [10]. The author's idea is to let a student, as a subject of educational and professional activities, manifest subjectivity in relation to the object, namely, professionally significant qualities of the person.…”
Section: Problem Backgroundmentioning
confidence: 99%
“…Its integral indicators and empirical values of t obtained are shown in Table 1. The T. Leary's Test questionnaire has never been used by other researchers for estimating activity and independence on the part of the students [5,7,10,44]. The chosen test reflected the interpersonal interaction in social environment.…”
Section: Values Of Activity and Independencementioning
confidence: 99%
See 1 more Smart Citation
“…Internationally, a few studies (Stouraitis et al, 2015;Park & De Costa, 2015;Said et al, 2014;Ares & Peercy, 2003) have suggested that crossing boundaries is a difficult task for teachers when being exposed to new teaching ways which constrain their teaching activity in different areas.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this level of understanding requires an analysis of the activities (Engeström, 2003) and tasks so that shared 'spaces' of understanding can be identified and used as a basis for constructing meanings for lasting understanding. Taken from business models Engeström's Activity Theory is a way to accessing pedagogical understandings and moving towards genuine communities of practice and 'authentic pedagogies' (Ares and Peercy, 2003;Wenger, 1998). In brief, authentic pedagogy makes explicit the relationships between action, experience and existing knowledge and the possibilities for further inquiry.…”
Section: Introductionmentioning
confidence: 99%